The Importance of Non-neuronal Cell Types in hiPSC-Based Disease Modeling and Drug Screening - Gonzalez, David M.; Gregory, Jill; Brennand, Kristen J. (Frontiers in Cell and Developmental Biology, 2017)
Current applications of human induced pluripotent stem cell (hiPSC) technologies in patient-specific models of neurodegenerative and neuropsychiatric disorders tend to focus on neuronal phenotypes. Here, we review recent efforts towards advancing hiPSCs toward non-neuronal cell types of the central nervous system (CNS) and highlight their potential use for the development of more complex in vitro models of neurodevelopment and disease. We present evidence from previous work in both rodents and humans of the importance of these cell types (oligodendrocytes, microglia, astrocytes) in neurological disease and highlight new hiPSC-based models that have sought to explore these relationships in vitro. Lastly, we summarize efforts towards conducting high-throughput screening experiments with hiPSCs and propose methods by which new screening platforms could be designed to better capture complex relationships between neural cell populations in health and disease.